2021
DOI: 10.1177/03331024211033551
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of treatment response in the child and adolescent migraine prevention (CHAMP) study: A randomized clinical trial

Abstract: Objective Identify preventive medication treatment response trajectories among youth participating in the Childhood and Adolescent Migraine Prevention study. Methods Data were evaluated from 328 youth (ages 8–17). Childhood and Adolescent Migraine Prevention study participants completed headache diaries during a 28-day baseline period and a 168-day active treatment period during which youth took amitriptyline, topiramate, or placebo. Daily headache occurrence trajectories were established across baseline and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(30 reference statements)
1
3
0
1
Order By: Relevance
“…In addition, acknowledging the limitations of missing data, we observed that the proportion of participants reporting at least 1 headache day per week continued to decline each week over the 8-week placebo run-in period. This is consistent with the trajectory of improvement in placebo-controlled trials in this age group, 1,14,17 hence the data here support the design of having used an 8-week placebo run-in period; however, knowing that many participants dropped out during this phase, future studies (utilizing diaries with higher adherence) could examine whether a shorter duration placebo run-in phase would improve power during the randomized phase.…”
Section: A Outcome Data For Placebo Versus Melatonin Groups Combinedsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, acknowledging the limitations of missing data, we observed that the proportion of participants reporting at least 1 headache day per week continued to decline each week over the 8-week placebo run-in period. This is consistent with the trajectory of improvement in placebo-controlled trials in this age group, 1,14,17 hence the data here support the design of having used an 8-week placebo run-in period; however, knowing that many participants dropped out during this phase, future studies (utilizing diaries with higher adherence) could examine whether a shorter duration placebo run-in phase would improve power during the randomized phase.…”
Section: A Outcome Data For Placebo Versus Melatonin Groups Combinedsupporting
confidence: 82%
“…Approximately 60%–70% of those treated with placebo can be expected to have a ≥50% reduction in their headache frequency 1 . Generally, a duration of 6–8 weeks of treatment is needed to determine whether a preventive will be effective for a child or adolescent with migraine 14 . Hence, the current study was designed with an 8‐week single‐blind placebo run‐in period with the aim of removing placebo responders before randomization.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty children and adolescents with primary headache disorders [51 females, 29 males, mean age (range) = 13.1 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years] participated in the study. The mean age in the olfactory training group was 13.83 years and in the control group was 12.38 years (p = 0.048).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, active pharmacological treatments show more side effects, which in turn lead to restrictions in daily life, compared to placebo. Response trajectories for therapy of children and adolescents with headaches show quick improvements ( 13 ). This positive aspect regarding the therapy of young headache patients should be taken into account in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Interessanterweise gibt es in verschiedenen klinischen Studien zur Migräneprophylaxe bei Kindern und Jugendlichen ähnliche Entwicklungen der Kopfschmerzhäufigkeit. Dabei zeigt sich eine relativ zügige Reduktion der Kopfschmerzfrequenz, unabhängig von der Intervention [ 58 ]. Bisher sind die Mechanismen dieser klinisch relevanten Verbesserung noch nicht ausreichend untersucht.…”
Section: Diskussionunclassified